Synthesis and Foaming Properties of New Cationic Surfactant with Multifunctional Groups - Zhang, Xin-Chun; Deng, Qiang; Chen, Gang (Asian Journal of Chemistry, 2015)
A new cationic surfactant (HECA) was synthesized and characterized. The conditions of in the quaterization reaction were investigated including the temperature, reaction time and molar ratio. The critical micelle concentration (CMC) and foamability and foam stability were evaluated and the results showed that it reaches to 32.1 mN/m at the concentration of 1 × 10-3 mol/L, the minimum surface tension was around 28.9 mN/m beyond 1 × 10-2 mol/L. The foam foamability and foam stability measurement are consistent with those of critical micelle concentration.